Alteration of Respirable Quartz Particle Cytotoxicity by Thermal Treatment in Aqueous Media - C. A. Hill; W. E. Wallace; M. J. Keane; S. J. Page; P. Bolsaitls (The National Institute for Occupational Safety and Health (NIOSH), 1988)
"Boiling respirable quartz dust in water for 10 to 40 minutes decreases the cytotoxicity for both erythrocyte hemolytic potential and pulmonary macrophage release of lactate dehydrogenase in vitro. The potential is reduced to near zero in the boiling concentration range of 1 to 10 mg quartz per ml water in boiling times of 20 to 40 minutes. Below this range the detoxification occurs over a longer boiling time. Above this range the hemolytic potential remaining after 40 minutes of boiling approaches native quartz potential with increasing concentration up to 30 mg quartz per ml water. Replacing the media with fresh at the midpoint of boiling results in full detoxification through 20 mg per ml. Pre—boiling the medium with quartz or silica gel reduces the effect of subsequently boiling test samples. Detoxification persists after mild drying at 110 C for 8 hours, and persists after three days of resuspension in water at room temperature. Additional data on persistence of the effect, on the use of acidic and basic media treatment, and on surface analyses are presented, with a discussion of a working hypothesis and research needs.IntroductionResearch underway to determine interactions of quarts and other mineral dust surfaces with pulmonary fluids and alveolar macrophages in culture led to the observation that when dusts were autoclaved in aqueous suspension, their cytotoxic effects on macrophages wore suppressed, in some cases fully and even after several days incubation with the cells. This finding was in direct contradiction to earlier results from both short term macrophage lysosaal enzyme release assays, as well as longer term cytotoxicity assays from macrophages in culture; in those studies, dusts were steam autoclaved at 121 121 ºC with no liquid water but with steam present. (1,2) However detoxification under boiling conditions has been reported in other research.(3). It was decided to use the hemolysis assay to further investigate these findings, because of its sensitivity, simplicity and cost."